The digger wasps of the genus Didineis Wesmael (Hymenoptera: Crabronidae: Bembicinae) of Russia and adjacent territories, with a key to species and new synonymies - Nemkov, Pavel G. (Zootaxa, 2015)
Ten species of Didineis Wesmael 1852 are recorded from Russia and adjacent territories. The new synonymy (valid name listed first) is established for Didineis bactriana Gussakovskij 1937 = D. ogloblini Gussakovskij 1937, D. clavimana Gussakovskij 1937 = D. turanica Gussakovskij 1937, and D. lunicornis (Fabricius 1798) = Didineis ruthenica Gussakovskij 1937. The number of valid species-group taxa in the genus Didineis is reduced to 25. The lectotypes are designated for four species: Didineis bactriana Gussakovskij 1937, D. botsharnikovi Gussakovskij 1937, D. clavimana Gussakovskij 1937, D. ruthenica Gussakovskij 1937. An original key to the species is provided.